2016
DOI: 10.1007/s00415-016-8330-x
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital and intra-hospital time delays in posterior circulation stroke: results from the Austrian Stroke Unit Registry

Abstract: Therapeutic effect of recombinant tissue-plasminogen activator (rt-PA) is time dependent. There is limited evidence whether localization of stroke within the posterior circulation (PCS) is associated with a treatment delay. We aimed to analyze within a nationwide multicenter cohort whether duration of pre- and intra-hospital patient management differs between patients with PCS and anterior circulation strokes (ACS). We studied onset-to-door-times (ODT) and door-to-needle-times (DNT) of all patients with acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 43 publications
1
35
3
1
Order By: Relevance
“…In the study of Sarikaya and co‐workers , time to treatment did not differ between patients treated with IVT for PCS and ACS, whilst other studies reported a significantly longer onset to needle time . In the present analysis, all relevant diagnostic and treatment‐related time periods were significantly longer in PCS patients treated with MT.…”
Section: Discussioncontrasting
confidence: 51%
“…In the study of Sarikaya and co‐workers , time to treatment did not differ between patients treated with IVT for PCS and ACS, whilst other studies reported a significantly longer onset to needle time . In the present analysis, all relevant diagnostic and treatment‐related time periods were significantly longer in PCS patients treated with MT.…”
Section: Discussioncontrasting
confidence: 51%
“…Posterior circulation LVOs are often more challenging to diagnose than LVOs of the anterior circulation due to a nonspecificity of associated symptoms, which can lead to significant delays in both prehospital and intrahospital management of this patient subset. 35 Nonetheless, common symptoms seen with occlusion of the VAs and BA include hemibody weakness or numbness, dizziness, nausea, vomiting, gait and balance issues, or alterations in consciousness. 36 Occlusions of the PCA typically result in contralateral vision changes such as a homonymous hemianopsia or quadrantanopia.…”
Section: Clinical Presentation Of Lvomentioning
confidence: 99%
“…Posterior circulation strokes have longer “door to needle” times for intravenous thrombolysis than anterior circulation strokes,1617 and are more likely to arrive in hospital after the 4.5 hour “time window” for thrombolysis 18…”
Section: Why Does This Matter?mentioning
confidence: 99%